(untitled) (Fiep Bulletin - online, 2011)
Environmental interference are factors that contribute to the changing situation of a healthy weight problems for overweight or underweight. With the help of anthropometric method, which appears as a tool for building tools based on mathematical models with high diagnostic power of various disorders of growth and development, this work, sectional and descriptive aims to propose a curve a reference BMI for age for adolescents from southern state of Sergipe, based on behaviors that influence the nutritional status of that population. The sample comprised 648 schoolchildren, was characterized as random and proportional by county, uniform and stratified by gender and age, class and intentional shift of classes with an average age of 16.50 ± 1.12 years. To determine the status of underweight and overweight was made use of BMI and was adopted as the reference for overweight and the 85th percentile for underweight 05. Of the subjects with changes in nutritional status is observed a higher incidence of overweight (> 8.50%) in both genders and all ages in relation to low birth weight (<3.09%). To determine the validity of the points proposed cuts were carried out with sensitivity and specificity. Studies on the prevalence of overweight and underweight and their relationship to socio-economic, environmental and physiological systems should be performed in various regions, thus generating better knowledge in order to drive adoption of guidelines and more effective strategy to combat to nutritional disorders.